2020
DOI: 10.1111/eci.13352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise programmes on pain, disease activity and function in ankylosing spondylitis: A meta‐analysis of randomized controlled trials

Abstract: Axial spondyloarthritis (SpA), affecting the axial skeleton, is the main form of chronic inflammatory disease. 1 The term axial SpA encompasses both patients with nonradiographic and radiographic axial SpA, which is also called as ankylosing spondylitis (AS). AS is an inflammatory disorder, resulting in the bony fusion of vertebral joints, which is the cause of chronic back pain. 1,2 It was reported that the prevalence of AS is 0.1-0.5%, and the female-to-male ratio is approximately 1:2. 1,3 Chronic back pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
3
13
1
Order By: Relevance
“…In a meta-analysis by Hu et al including 10 studies and 534 AS patients, the exercise group had statistically significant improvements in pain, BASDAI, and BASFI scores compared to the non-exercise group. 18 In our study, it was found that 6-week home exercise program improved BASDAI and BASFI scores significantly more in the anti-TNF alpha group than in the non-anti-TNF group. Although there was an improvement in VAS-spinal pain scores in the anti-TNF alpha group, it was not statistically significant.…”
Section: Anti-tnf Alpha Group (N=23)supporting
confidence: 44%
See 1 more Smart Citation
“…In a meta-analysis by Hu et al including 10 studies and 534 AS patients, the exercise group had statistically significant improvements in pain, BASDAI, and BASFI scores compared to the non-exercise group. 18 In our study, it was found that 6-week home exercise program improved BASDAI and BASFI scores significantly more in the anti-TNF alpha group than in the non-anti-TNF group. Although there was an improvement in VAS-spinal pain scores in the anti-TNF alpha group, it was not statistically significant.…”
Section: Anti-tnf Alpha Group (N=23)supporting
confidence: 44%
“…Improvements in BASDAI, BASFI, and VAS-spinal pain scores in both groups were in accordance with these meta-analyses. 17,18 BASDAI and VAS-spinal pain baseline mean values were significantly lower in the anti-TNF alpha group, than in the non-anti-TNF alpha group. At the end of the treatment, the change in BASDAI and VASspinal pain mean values was found to be lower in the anti-TNF alpha group, compared to the non-anti-TNF alpha group.…”
Section: Anti-tnf Alpha Group (N=23)mentioning
confidence: 69%
“…Key phrases for database screening were: ankylosing spondylitis + exercise; axial spondyloarthritis + exercise; ankylosing spondylitis + physical activity; axial spondyloarthritis + physical activity. Backward and forward citation chasing was also undertaken with identified reviews from 2018 onward 13‐16 …”
Section: Methodsmentioning
confidence: 99%
“…However, exercise recommendations for people with AS 12 are ambiguous, with no guidance on factors such as mode, intensity or duration -advice that reflects the equivocality of existing evidence. Two recent systematic reviews 13,14 along with a 2019 Cochrane Review, 15 concluded that exercise training programs did not reduce levels of CRP or ESR compared to usual care, although seemingly incongruently, BASDAI measures improved. However, these reviews synthesized all modes of exercise including aerobic, rangeof-motion and resistance training, quantitatively analyzing and basing conclusions on heterogenous exercise programs.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recommended that the quality of interventions in exercise trials for patients with AS can be improved and that future trials should focus on measuring and reporting physiological responses and adherence to exercise intervention (Daginfrud et al 2011). A recent meta-analysis of randomised controlled trials on the effects of exercise programmes in AS patients concluded that further studies are needed to investigate the effects of specific exercise interventions on pain, quality of life, function and disease activity (Hu et al 2020). Our study aimed to determine the effects of a 6-month swimming, land-based stretching, strengthening and breathing exercise intervention on disease activity, physicaland functional-parameters in patients with AS by comparing an exercise group (ASE) with a control group (ASC).…”
Section: Introductionmentioning
confidence: 99%